Discerning the survival advantage among patients with prostate cancer who undergo radical prostatectomy or radiotherapy: The limitations of cancer registry data. Issue 9 (18th January 2017) - Williams, Stephen B.; Huo, Jinhai; Chamie, Karim; Smaldone, Marc C.; Kosarek, Christopher D.; Fang, Justin E.; Ynalvez, Leslie A.; Kim, Simon P.; Hoffman, Karen E.; Giordano, Sharon H.; Chapin, Brian F.
Abstract : BACKGROUND: The objective of this study was to compare the overall survival of patients who undergo radical prostatectomy or radiotherapy versus noncancer controls to discern whether there is a survival advantage according to prostate cancer treatment and the impact of selection bias on these results. METHODS: A matched cohort study was performed using the Surveillance, Epidemiology, and End Results (SEER)‐Medicare–linked database. In total, 34, 473 patients ages 66 to 75 years were identified who were without significant comorbidity, were diagnosed with localized prostate cancer, and received treatment treated with surgery or radiotherapy between 2004 and 2011. These patients were matched to a noncancer control cohort. The rates of all‐cause mortality that occurred within the study period were compared. Cox proportional hazards regression analysis was used to identify determinants associated with overall survival. RESULTS: Of 34, 473 patients who were included in the analysis, 21, 740 (63%) received radiation therapy, and 12, 733 (37%) underwent surgery. There was improved survival in patients who underwent surgery (hazard ratio, 0.35; 95% confidence interval, 0.32‐0.38) and in those who received radiotherapy (hazard ratio, 0.72; 95% confidence interval, 0.68‐0.75) compared with noncancer controls. Overall survival improved significantly in both treatment groups, with the greatest benefit observed among patients who underwent surgery (log rank P  < .001). CONCLUSIONS: Population‐based data indicated that patients with prostate cancer who received treatment with either surgery or radiotherapy had improved overall survival compared with a cohort of matched noncancer controls. Surgery produce longer survival compared with radiation therapy. These results suggest an inherent selection‐bias because of unmeasured confounding variables. Cancer 2017;123:1617–1624. © 2017 American Cancer Society . Abstract : The treatment of localized prostate cancer using either surgery or radiotherapy is associated with an improved overall survival benefit compared with noncancer controls. There is inherent selection bias because of unmeasured confounding variables when using cancer registry data.